O processo de institucionalização de novas práticas de controles de gestão em pequenos empreendimentos - Bueno, Maria Elena Amaral Ferreira (2019)
This study aims to analyze how the process of institutionalization of new management control practices in small enterprises occurs. The phenomenon of change in management accounting, especially the forces and logics that potentiate or compromise the process, are analyzed on the basis of institutional theory, the approaches of the old institutional economy and the new institutional sociology. The theoretical models used for the institutionalization process are the expansion proposed by Bogt and Scapens (2014) to the Burns and Scapens (2000) model and the Tolbert and Zucker (1999) model. To achieve the proposed objective, this research is outlined by the interpretative perspective, with qualitative approach and descriptive nature, through a multiple case study with two small companies assisted by the Project of Extension and Innovation Project of the University of Passo Fundo. Data were collected through semi-structured interviews with the owner director and two managers of each company, totaling six participants. In addition, several documents were analyzed and non-participant observation was carried out on company premises. Data were analyzed through content analysis with the aid of Atlas.ti 8.0® software. The results found revealed that in both companies, in addition to external pressures arising from the market and specific legislation, there was the presence of hierarchical power driving change. However, different types of rationality were applied from the implementation of the Quality Management System, some enhancing the process, such as managers and sector managers, others compromising, as the resistance of operational actors, motivated by the conflict of interests and divergence in the interpretation of the meaning of this new practice. These results confirm previous research by revealing that change occurs through a mix of external and internal factors, which face internal resistance. From power relations to personal interests, resistance involves several factors, with more or less intensity, constituting a natural element of the human being. However, they do not always prevent the implementation of the new practice. Of the companies studied, one managed to overcome initial resistance and succeeded in implementation, while the other needed to halt the process. Therefore, it can be deduced that both the factors that empower and those that compromise change have their intensity, varying according to the organizational context, proving previous studies that argue that each organization can respond differently in the same institutionally complex field. The findings of this study provide small business managers with subsidies that may be useful in implementing new management controls. Understanding external and internal factors that favor or resist the process can help achieve successful change, contribute to action planning, and optimize resources. Knowing the different rationalities present in the organization and managing these elements in a holistic way, can contribute to possible resistances that are preventively remedied, the shared meanings and the new consolidated practice.